Ibn Rushd’s (Averroes) Philosophy of Religion - Malikov, Aladdin (Scholarya Demo Journal of Ruby, 2018)
Religious and philosophical relations are currently considered as the main and important subject of philosophy of religion. Ibn Rushd, the representative of Islamic peripatetism, has a great role in shaping the Muslim renaissance. For this reason, the place and role of philosophy of religion in Ibn Rushd’s philosophy is chosen as the subject of the article. The article first studies Ibn Rushd’s scientific work and their philosophical significance and then examines the place and role of philosophy and generally, religious and philosophical relations in the philosophy of Ibn Rushd. Sharia’s attitude toward philosophy has been analyzed both from religious and philosophical point of view. Religious and philosophical relations in Ibn Rushd’s philosophy, the unity and division of faith and mind, solutions to the contradictions and Ibn Rushd’s answer to the remarks are given here. Ibn Rushd’s Latin followers’ views, the theory of double truth, as well as, evaluation and analysis of this approach have been revealed in conclusion.